2012
DOI: 10.2174/138920012802138660
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFR Somatic Mutations in Non-Small Cell Lung Cancer (NSCLC) Using a Novel Mutant-Enriched Liquidchip (MEL) Technology

Abstract: We have developed and standardized a novel technology, mutant-enriched liquidchip (MEL), for clinical detection of EGFR mutations. The MEL integrates a mutant-enriched PCR procedure with liquidchip technology for detections of EGFR exon 19 deletions and L858R mutation on both formalin-fixed and paraffin-embedded (FFPE) slides and plasma samples from patients with non-small cell lung cancer (NSCLC). The detection sensitivity was 0.1% of mutant DNA in the presence of its wild-type DNA. The cross-reaction rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…However, it is 59 in our study, which is much lower than 71. Although the median age in Asia has been reported as lower than 71 before (Xu et al , 2011; Zhang et al , 2012), more young patients with NSCLC in China than the western countries may be the reason for the low median age. According to an internet database from 1381 hospitals, there is only 0.7% lung cancer at the age group <40 years (Age Group of Lung Cancer Diagnosed, 2000–2007).…”
Section: Discussionmentioning
confidence: 83%
“…However, it is 59 in our study, which is much lower than 71. Although the median age in Asia has been reported as lower than 71 before (Xu et al , 2011; Zhang et al , 2012), more young patients with NSCLC in China than the western countries may be the reason for the low median age. According to an internet database from 1381 hospitals, there is only 0.7% lung cancer at the age group <40 years (Age Group of Lung Cancer Diagnosed, 2000–2007).…”
Section: Discussionmentioning
confidence: 83%
“…As shown in Figure 1, after primary screening, 34 full-text articles10131415162223242526272829303132333435363738394041424344454647484950 were selected for further evaluation of eligibility. By rigorous evaluation, 20 eligible studies were identified and included in meta-analysis1314151622232425262728293031323334353637.…”
Section: Resultsmentioning
confidence: 99%
“…For patients who provided pretreatment samples, the presence of EGFR mutations in blood may correlate with severe tumor burden, which contributes to higher proportion of tumor-derived cfDNA. Zhao et al and Zhang et al found that there were more detectable EGFR mutations in plasma from patients with advanced disease or patients with poorly differentiated tumors [21], [35]. Park et al reported that tumor burden was predictive of inferior survival in NSCLC patients with EGFR mutant tumor who received gefitinib [36].…”
Section: Discussionmentioning
confidence: 99%